2016
DOI: 10.1159/000443536
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteral Reflux and Renal Scarring Risk in Children after the First Febrile Urinary Tract Infection

Abstract: Background/Aims: There are many controversies regarding the best approach for evaluating children after their first febrile urinary tract infection (UTI). The aim of this study was to define the clinical, laboratory, and radiological features of patients with their first febrile UTI and to investigate the factors that might predict the presence of vesicoureteral reflux (VUR) and renal scarring. Methods: The files of patients who were followed due to their first febrile UTI between 2008 and 2013 were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…Hydronephrosis was the most common ultrasound finding, whereas bladder cystitis, which is of pathophysiologic importance, was found significantly more common in patients with the recurrent episode. In line with our findings, Yilmaz et al [11] reported that recurrent urinary tract infections were significantly more common in patients with renal scarring and structural abnormalities. The authors reported that the rate of recurrent infection was as high as 55%, and the presence of an ultrasound abnormality was 41.2% in children older than five years.…”
Section: Discussionsupporting
confidence: 93%
“…Hydronephrosis was the most common ultrasound finding, whereas bladder cystitis, which is of pathophysiologic importance, was found significantly more common in patients with the recurrent episode. In line with our findings, Yilmaz et al [11] reported that recurrent urinary tract infections were significantly more common in patients with renal scarring and structural abnormalities. The authors reported that the rate of recurrent infection was as high as 55%, and the presence of an ultrasound abnormality was 41.2% in children older than five years.…”
Section: Discussionsupporting
confidence: 93%
“…One should suspect urinary tract anatomic abnormalities including vesicoureteral reflux if recurrent infections start in infancy in either gender (1,2). Children of all ages with urinary instrumentation or a urinary catheter are prone to iatrogenic UTIs as these procedures or instruments facilitate bacterial entry into the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Renal scar was identified in half of patients (57%) who had experienced UTI and had DMSA performed. It is higher when compared to results of a study carried out in normal Turkish society (20). This situation can probably be associated with increased expression of a number of genes coding transcriptional factors as a result of interactions of calcium oxalate monohydrate crystals with epithelial cells, extracellular matrix regulators and growth factors (21).…”
Section: Discussionmentioning
confidence: 72%